The Correlation Students’ Motivation Toward Students’ Writing Ability In English Learning Achievements - Wiriawan, I Ketut (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research examined the correlation students’ motivation toward students’ writing ability in English language learning. This research aimed the correlation students' motivation toward students' writing ability in English language learning. This research was a quantitative analysis with a type of non-experimental research and the design used was an ex post-facto research. The population of this research was tenth-grade students at SMK Negeri 1 Kubu, divided into 16 study groups with a total population of 491 students. The sampling technique used in this research refers to the Slovin formulation in selecting the number of the sample used. Random sampling technique were used with a total number of 84 students were being sample in this research. The data of students’ motivation were collected through research instrument where the questionnaires were used to collect the data. The reliability tests were conducted before collecting the data. Based on the analysis, the reliability test values were 0.895. The students’ writing ability was measured by conducting a test. The data were analyzed by Pearson Product Moment Correlation, SPSS 23.00 application for Windows were used in analyzing the data. The obtained data showed a coefficient of 0.200. Based on the coefficient of test normality, where the coefficient were higher than 0.05. The linearity test were conducted, the analysis of linearity test showed the coefficients of 0.589, it can be stated that the data were a linear regression. The results of the analysis of the correlation showed a Sig. (2-tailed) value of 0.946, with a Pearson Correlation value of 0.007. Based on the results of the correlation analysis, it could be concluded that the data does not have a significant correlation because the test results have a value higher than the threshold (sig 0.05). Referring to the results of this research, it could be concluded that the students’ motivation have no significant correlation toward students’ writing ability. Based on the results of the analysis, the high and low motivation of students has not affected the students’ writing ability.